PCT Symmetric Black Hole Radiation from Semiclosed Friedman Universe and Zitterbewegung of Radiating Particle (Global Journal of Science Frontier Research, 2015)
Einstein's early thought experiment of a tiny clock ticking (quantized) around a closed loop in Newton potential-GM/r (gravitational Bohr atom), is revisited and its cosmological implication is considered by first replacing the point mass M by a magnetc flux confined within a slender tube standing perpendicular to the plane of the paper, indicating probable existence of a pair of magnetic monopoles at the north and the south poles of the double-valued Friedman universe projected on 2-dimensional plane. The clock is next replaced by a wavelike test particle ticking with Planck period and the Newtonian mass M by a Planck scale proper mass of the semiclosed Friedman black hole joined onto asymptotically flat outer space in early and later inflationary epochs of expanding and contracting universe, emitting radiation from P (left-right)-C (particle-antiparticle) and T(future-past) symmetric path of the test particle zigzagging in time (Zitterbeweging). A direct imaging of trembling motion of a laser-activated ion clock trapped by strong electrodynamic potential in Bose-Einstein condensates, simulating Dirac's monopole and Zitterbewegung, followed by energy emission, simulating Hawking radiation, is briefly mentioned.
Keywords: quantum theory; general relativity; cosmology; black hole; dark energy